2019
DOI: 10.3390/molecules24132492
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Synthetic Characteristics of Biomass-Derived Isosorbide-Based Poly(arylene ether ketone)s for Sustainable Super Engineering Plastic

Abstract: Demand for the development of novel polymers derived from biomass that can replace petroleum resources has been increasing. In this study, biomass-derived isosorbide was used as a monomer in the polymerization of poly(arylene ether ketone)s, and its synthetic characteristics were investigated. As a phase-transfer catalyst, crown ether has increased the weight-average molecular weight of polymers over 100 kg/mol by improving the reaction efficiency of isosorbide and minimizing the effect of moisture. By control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Sorbitol and mannitol can be used as the precursor compounds of isosorbide, lactic acid, and 1,4-sorbitan [ 104 – 106 ]. Isosorbide is a commercial platform chemical that is usually used as a precursor to synthesize isosorbide-based polymers, such as poly(arylene ether ketone)s, a type of super-engineered plastic [ 107 ], and some polymeric nanofibres that can be used in industrial applications [ 108 ]. In addition, isosorbide can be further converted into hexanol, hexane, and pentane [ 109 ].…”
Section: Products Derived From Plant Biomassmentioning
confidence: 99%
“…Sorbitol and mannitol can be used as the precursor compounds of isosorbide, lactic acid, and 1,4-sorbitan [ 104 – 106 ]. Isosorbide is a commercial platform chemical that is usually used as a precursor to synthesize isosorbide-based polymers, such as poly(arylene ether ketone)s, a type of super-engineered plastic [ 107 ], and some polymeric nanofibres that can be used in industrial applications [ 108 ]. In addition, isosorbide can be further converted into hexanol, hexane, and pentane [ 109 ].…”
Section: Products Derived From Plant Biomassmentioning
confidence: 99%
“…The unique structure and stereoisomerism found in natural compounds provide researchers with a strategic advantage in their endeavor toward creating mechanically robust materials in which stereochemistry can define the behavior. , Rigid-ring bicyclic ethers obtained from the dehydrative cyclization of sugar hexitols have garnered substantial attention as monomers because of their unique structural features, imparting geometric isomerism (Scheme ). While the most prevalent of the biosourced cyclic units is the glucose-derived isosorbide, which is exemplified by its ubiquitous presence throughout polymer chemistry, , the accompanying stereoisomers, isomannide and isoidide, have received less attention. Some historic and recent studies have reported the synthesis of isomannide- and isoidide-containing polymers, but most lack detailed thermal and/or mechanical characterization to fully elucidate the influence of the stereochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Park et al developed an isosorbide‐based polysulfone (PSU) with outstanding thermal and mechanical properties (Figure 1B). [ 18,19 ] Epps et al recently published a patent disclosing the structure of a bis(guaiacol)‐based PSU. [ 20 ] To the best of our knowledge, these are the only examples of PSU‐bearing aliphatic aromatic moieties from renewably derived monomers.…”
Section: Introductionmentioning
confidence: 99%